2017
DOI: 10.1177/0003702817717969
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Behavior of White Pigment Mixtures Using Reflectance, Ultraviolet—Fluorescence Spectroscopy, and Multispectral Imaging

Abstract: Reflectance spectroscopy, ultraviolet (UV)-fluorescence spectroscopy, and multispectral imaging have been widely employed for pigment identification on paintings. From ancient times to the present, lead white, zinc white, and titanium white have been the most important white pigments used for paintings and they are used as pigment markers for dating a work of art. The spectral behavior of these pigments is reported in several scientific papers and websites, but those of their mixtures are quite unknown. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Similar results have been obtained in previous studies, 4,9 in which titanium dioxide in the rutile crystal form was identified as one of the major components in various spray paints and street art graffiti samples. The use of titanium white is confirmed by the registered reflectance spectra for the white and light shades (Figure 1A) that show a characteristic steep rise with an inflection point around 410 nm 20 . Within the FTIR data, the presence of titanium white can be inferred based on the broad absorption in the lower wavenumber range 4 (750‐400 cm −1 ).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Similar results have been obtained in previous studies, 4,9 in which titanium dioxide in the rutile crystal form was identified as one of the major components in various spray paints and street art graffiti samples. The use of titanium white is confirmed by the registered reflectance spectra for the white and light shades (Figure 1A) that show a characteristic steep rise with an inflection point around 410 nm 20 . Within the FTIR data, the presence of titanium white can be inferred based on the broad absorption in the lower wavenumber range 4 (750‐400 cm −1 ).…”
Section: Resultsmentioning
confidence: 60%
“…The use of titanium white is confirmed by the registered reflectance spectra for the white and light shades ( Figure 1A) that show a characteristic steep rise with an inflection point around 410 nm. 20 Within the FTIR data, the presence of titanium white can be inferred based on the broad absorption in the lower wavenumber range 4 (750-400 cm −1 ).…”
Section: Inorganic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is very useful to recognize pigments which have large differences in the IR absorbance, although they appear similar to the eye (i.e., lapis lazuli shows a red false-color with respect to the much less expensive azurite that looks blue [20]). However, since any combination of three different images (not mandatorily corresponding to the ones just mentioned) could be defined as "False-color image", new perspectives are open to image processing, not necessarily involving IR range but aiming to underline different spectral features even in the visible range [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years, hyperspectral and multispectral imaging technique has been widely used for the imaging of fine art paintings [17,20] and ancient documents, aiming at the analysis of the materials used [21,22] and the digital restoration of degraded or erased parts [23]. Hyperspectral and multispectral imaging has been developed by combining both digital imaging and spectroscopy.…”
Section: Introductionmentioning
confidence: 99%